(untitled) - Dale, Nell B. (Lexington, Mass, 1995)
Thoroughly revised and updated to reflect recent changes in software engineering, Introduction to Turbo Pascal and Software Design, Fourth Edition retains the excellent pedagogy, outstanding clarity, and balanced presentation that marked earlier editions as leaders in computer science education. An emphasis on problem solving and algorithmic design teaches students to implement programs most effectively. A sensible organization introduces concepts where students need them most, and an extensive and varied selection of exercises and Case Studies supports and strengthens concepts learned. In addition, all programming examples follow well-defined methodologies that reinforce proper problem-solving principles. In this edition, new chapters provide greater emphasis on implementing abstract data types to make the most of the power of Turbo Pascal, while a reorganization of chapters streamlines the presentation. Explanations and examples using Turbo Pascal 7.0 are integrated throughout, and all programs have been tested in Turbo. Augmented coverage of topics such as encapsulation of data types as both units and objects and object-oriented programming gives students a current, usable introduction to modern software engineering principles.
Keywords: Pascal (Computer program language),Ngôn ngữ lập trình pascal